Using Dynamic Facade for IAQ, Thermal Comfort and Energy Efficient air Conditioning (University of Khartoum Engineering Journal, 2022)
:The built environment has a direct impact on Qatar's natural environment, the economy and human health.Qatar is the largest consumer of energy per capita in the world, the fourth country in the world that produces lesswater from freshwater resources and so relies essentially on desalination for domestic water supplies. QatarSustainability Assessment System (QSAS) is a performance-based sustainability rating system which aims to create asustainable urban environment that reduce environmental impacts while satisfying local community needs. In additionto addressing all locally relevant aspects of sustainability, ecological impact, and green building design criteria, QSASdeveloped a standalone building energy standard to support Qatar’s building energy ratings. QSAS adopted the EPCCEN standard and EPC approach for the Qatar energy code development and some normative parameters used inCEN standards were changed for the use in the Qatar local environment. It complies with the global trend towardsperformance-based code; using standardised normative calculation methods. The simplified calculation is preferred asit requires less input data, no deep simulation expertise and leads to transparent readily understandable calculations.Buildings, new and old, account for 50% of global energy consumption and related emissions. This figure rises tomore than 70% for the Gulf Region. Estimates of the cut in carbon emissions needed within our lifetime to avertcatastrophic climate change range from 60% to 80% of current demand. Buildings thus present both a majorimpediment to reducing our reliance on the burning of dwindling reserves of fossil fuel and a real opportunity forachieving significant reduction in global carbon emissions. Dynamic facade, using Dynamic Insulation (DI), is anenergy-efficient method of supplying pre-tempered, filtered ventilation air to a building through an air-permeable,dynamically insulated envelope or facade. One of the important features of DI is that it effectively decouplesventilation rate from energy use. In theory, it should work well with all buildings, including homes, schools, officesand sports facilities where high occupancy is the norm. Our paper investigates the use of DI in a building facade forzone local insulation and ventilation. The savings in energy and CO2 reduction are quantified against existingstandards in the Gulf Region. The results show that DI can provide tempered fresh air, raise energy efficiency andreduce air conditioning energy demand without compromising Indoor Air Quality (IAQ) or thermal comfort level.